Intracochlear Recordings of Acoustically and Electrically Evoked Potentials in Nucleus Hybrid L24 Cochlear Implant Users and Their Relationship to Speech Perception - Kim, Jae-Ryong; Tejani, Viral D.; Abbas, Paul J.; Brown, Carolyn J. (Frontiers in Neuroscience, 2017)
The Hybrid cochlear implant (CI) has been developed for individuals with high frequency hearing loss who retain good low frequency hearing. Outcomes have been encouraging but individual variability is high; the health of the cochlea and the auditory nerve may be important factors driving outcome. Electrically evoked compound action potentials (ECAPs) reflect the response of the auditory nerve to electrical stimulation while electrocochleography (ECochG) reflects the response of the cochlear hair cells and auditory nerve to acoustic stimulation. In this study both ECAPs and ECochG responses were recorded from Nucleus Hybrid L24 CI users. Correlations between these two measures of peripheral auditory function and speech perception are reported. This retrospective study includes data from 25 L24 CI users. ECAPs and ECochG responses were recorded from an intracochlear electrode using stimuli presented at or near maximum acceptable loudness levels. Speech perception was assessed using Consonant-Nucleus-Consonant (CNC) word lists presented in quiet and AzBio sentences presented at a +5 dB signal-to-noise ratio in both the combined acoustic and electric (A+E) and electric (E) alone listening modes. Acoustic gain was calculated by subtracting these two scores. Correlations between these physiologic and speech perception measures were then computed. ECAP amplitudes recorded from the most apical electrode were significantly correlated with CNC scores measured in the E alone (r=0.56) and A+E conditions (r=0.64), but not with performance on the AzBio test. ECochG responses recorded using the most apical electrode in the intracochlear array but evoked using a 500 Hz tone burst were not correlated with either the scores on the CNC or AzBio tests. However, ECochG amplitude was correlated with a composite metric relating the additional benefit of acoustic gain in noise relative to quiet conditions (r=0.67). Both measures can be recorded from Hybrid L24 CI users and both ECAP and ECochG measures may result in more complete characterization of speech perception outcomes than either measure alone.